Functional differences between antiviral activities of sulfonated and intact intravenous immunoglobulin preparations toward varicella-zoster virus and cytomegalovirus. Issue 6 (June 2015) - Yajima, Misako; Shiraki, Atsuko; Daikoku, Tohru; Oyama, Yukari; Yoshida, Yoshihiro; Shiraki, Kimiyasu
Abstract: Intravenous immunoglobulin (IVIG) is used to treat severe viral infection, especially varicella-zoster virus (VZV) and cytomegalovirus (CMV) infections. The neutralization antibody titers of eleven IVIG preparations from four companies were examined using VZV and CMV with and without complement. The neutralizing antibody titers of intact IgG preparations were three to six times higher after addition of complement. The effectiveness of the sulfonated IgG preparation was not enhanced by complement, but desulfonated IgG regained enhanced neutralization activity with complement. Antibody-dependent cellular cytotoxicity (ADCC) toward VZV-infected cells was observed with both intact and sulfonated IVIG and guinea pig splenocytes, but ADCC toward CMV-infected cells was not, although NK cell activity toward cells infected with VZV or CMV was detected by splenocytes. Sulfonated IVIG had no complement-activated neutralization of VZV and CMV but retained ADCC toward VZV with less activity after dilution than with intact IVIG. Because sulfonated IVIG is converted to the intact form after intravenous administration, it would show complement-enhanced neutralization and ADCC activity similar to that of intact IVIG in vivo . In this study we showed the effects of intact and sulfonated IgG on the functional activity of IgG against VZV and CMV.